GAMBARAN POLA MAKAN TERHADAP STATUS GIZI SISWA DI SD PUTRA INDONESIA SURABAYA - Merry Sunaryo (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
Nutrition problems faced by the Indonesian nation has become more complete with many nutritional problems in children. Basic Health Research Data (RISKESDAS) in 2010 shows that Indonesia nutritional status of children aged 6-18 years as much as 35.4% is very short, as many as 66.6% are classified as short, as many as 4.6% are very thin as 9.1%, As much as 22.1% and as much as 13.1% belong to the fat. This research is an observational research and descriptive research with cross sectional design and by using quantitative approach. The sample in this research is the students of grade 4, 5, and 6 SD Putra Indonesia. The number of samples is 93 students which the total sampling method, the use of this method because the population number is not more than 100 people. The results obtained most of the diet respondents in general that most do not do breakfast, do not bring food supplies to school and like snack at school. Based on the results of assessment of nutritional status obtained information that the nutritional status of respondents based on BMI assessment If the calculated number of students with abnormal weight that is equal to 58.1%. Participants who had BMI assessment with normal weight category were 39 people (41.9%). Therefore, it is known that most students have an abnormal BMI. Generally, it takes considerable extra attention for parents and teachers to be able to monitor children in the intake of nutrition and healthy eating patterns. In order to improve the nutritional status of children who are now in its infancy.